Continuous reform of vocational training in Spain, or the paradox between school integration and segregation - Merino, Rafael (Education Policy Analysis Archives, 2013)
Successive reforms of vocational training face a paradox: if vocational training is defined as a track separate from the academic one, then it will be socially devalued and marked with a strong social bias. If the vocational and academic tracks are integrated in one comprehensive curriculum then practices of teachers and students make facto incorporation of different ways for students with poor school performance. This article discusses how vocational training was designed in the secondary education framework in the two main reforms carried out in Spain in 1970 and 1990, and how the expectations of policy-makers and the actions of the actors could mismatch. The paper includes a reflection on the last proposal for new educational reform by the Spanish government, the draft of LOMCE 2012.